The Restriction of Suffrage in the Perspective of Fair Election in Indonesia - Khairul Fahmi; Zainal Arifin Mochtar; Saldi Isra; Zulkifli Aspan (Faculty of Law, Hasanuddin University, 2018)
In order to ensure the suffrage of citizens is implemented according to the principle of fair election, regulations on general and local elections may contain various kinds of restriction of suffrage. The rights to vote as well as be voted must be restricted in a way that the process of election may run seamlessly and generate a government capable of exercising the mandate of the people. However, such restriction must be performed in a fair and proportionate manner. The restriction must not cause uncertainty or even distinction of treatment towards the citizens. By means of normative legal research, this research comes to a conclusion that restriction of suffrage in general and local elections have yet been performed fairly. Legal uncertainty in the restriction of suffrage still occurs. Simultaneously, different treatment towards citizens who intend to nominate themselves is still contained in the norms related to the requirements to vote and be voted.